KARAKTERISTIK SPASIAL DAN POTENSI CADANGAN KARBON DI BENTANG ALAM MBELILING NUSA TENGGARA TIMUR - Oktian, Serlina H.; Setyaningsih, Luluk; Anen, Nengsih; Adinugroho, Wahyu C. (Jurnal Nusa Sylva, 2021)
Providing comprehensive information on carbon stock data on all carbon pools needs to be done to plan and measure climate change mitigation efforts that are carried out. This research was conducted by analyzing spatial characteristics and estimating carbon stocks with model development. Spatial analysis is carried out to provide an overview of the distribution of spatial values that can use the built model. Estimation of carbon stock is carried out by building a carbon stock estimator model that correlates the value of remote sensing parameters with the value of carbon stocks in all carbon storage sources. The characteristics of the vegetation index value in the forest category are greater than in the non-forest category and vice versa for the distribution of the digital number average value. The model development is only carried out on aboveground biomass and belowground biomass carbon pools. The results of the analysis of the estimation of carbon stocks based on the selected model showed the potential for aboveground biomass was 5,200,841.45 tC and the potential for belowground biomass was 1,317,948.10 tC.